Proceedings of the 4th World Conference on Research Integrity. Issue 1 (July 2016) - O'Brien, Susan; Chan, Danny; Leung, Frederick; Ko, Eun; Kwak, Jin; Gwon, TaeHwan; Lee, Ji; Lee, Min-Ho; Nolte, Helga; Gommel, Michael; Sponholz, Gerlinde; Krastev, Yordanka; et al.
Table of contents I1 Proceedings of the 4th World Conference on Research Integrity Concurrent Sessions: 1. Countries' systems and policies to foster research integrity CS01.1 Second time around: Implementing and embedding a review of responsible conduct of research policy and practice in an Australian research-intensive university Susan Patricia O'Brien CS01.2 Measures to promote research integrity in a university: the case of an Asian university Danny Chan, Frederick Leung 2. Examples of research integrity education programmes in different countries CS02.1 Development of a state-run "cyber education program of research ethics" in Korea Eun Jung Ko, Jin Sun Kwak, TaeHwan Gwon, Ji Min Lee, Min-Ho Lee CS02.3 Responsible conduct of research teachers' training courses in Germany: keeping on drilling through hard boards for more RCR teachers Helga Nolte, Michael Gommel, Gerlinde Sponholz 3. The research environment and policies to encourage research integrity CS03.1 Challenges and best practices in research integrity: bridging the gap between policy and practice Yordanka Krastev, Yamini Sandiran, Julia Connell, Nicky Solomon CS03.2 The Slovenian initiative for better research: from national activities to global reflections Ursa Opara Krasovec, Renata Sribar CS03.3 Organizational climate assessments to support research integrity: background of the Survey of Organizational Research Climate (SOuRCe) and the experience with its use at Michigan State University Brian C. Martinson, Carol R. Thrush, C.K. Gunsalus 4. Expressions of concern and retractions CS04.1 Proposed guidelines for retraction notices and their dissemination Ivan Oransky, Adam Marcus CS04.2 Watching retractions: analysis of process and practice, with data from the Wiley retraction archives Chris Graf, Verity Warne, Edward Wates, Sue Joshua CS04.3 An exploratory content analysis of Expressions of Concern Miguel Roig CS04.4 An ethics researcher in the retraction process Michael Mumford 5. Funders' role in fostering research integrity CS05.1 The Fonds de Recherche du Québec's institutional rules on the responsible conduct of research: introspection in the funding agency activities Mylène Deschênes, Catherine Olivier, Raphaëlle Dupras-Leduc CS05.2 U.S. Public Health Service funds in an international setting: research integrity and compliance Zoë Hammatt, Raju Tamot, Robin Parker, Cynthia Ricard, Loc Nguyen-Khoa, Sandra Titus CS05.3 Analyzing decision making of funders of public research as a case of information asymmetry Karsten Klint Jensen CS05.4 Research integrity management: Empirical investigation of academia versus industry Simon Godecharle, Ben Nemery, Kris Dierickx 5A: Education: For whom, how, and what? CS05A.1 Research integrity or responsible conduct of research? What do we aim for? Mickey Gjerris, Maud Marion Laird Eriksen, Jeppe Berggren Hoej CS05A.2 Teaching and learning about RCR at the same time: a report on Epigeum's RCR poll questions and other assessment activities Nicholas H. Steneck CS05A.4 Minding the gap in research ethics education: strategies to assess and improve research competencies in community health workers/promoteres Camille Nebeker, Michael Kalichman, Elizabeth Mejia Booen, Blanca Azucena Pacheco, Rebeca Espinosa Giacinto, Sheila Castaneda 6. Country examples of research reward systems and integrity CS06.1 Improving systems to promote responsible research in the Chinese Academy of Sciences Ding Li, Qiong Chen, Guoli Zhu, Zhonghe Sun CS06.4 Exploring the perception of research integrity amongst public health researchers in India Parthasarathi Ganguly, Barna Ganguly 7. Education and guidance on research integrity: country differences CS07.1 From integrity to unity: how research integrity guidance differs across universities in Europe. Noémie Aubert Bonn, Kris Dierickx, Simon Godecharle CS07.2 Can education and training develop research integrity? The spirit of the UNESCO 1974 recommendation and its updating Daniele Bourcier, Jacques Bordé, Michèle Leduc CS07.3 The education and implementation mechanisms of research ethics in Taiwan's higher education: an experience in Chinese web-based curriculum development for responsible conduct of research Chien Chou, Sophia Jui-An Pan CS07.4 Educating principal investigators in Swiss research institutions: present and future perspectives Louis Xaver Tiefenauer 8. Measuring and rewarding research productivity CS08.1 Altimpact: how research integrity underpins research impact Daniel Barr, Paul Taylor CS08.2 Publication incentives: just reward or misdirection of funds? Lyn Margaret Horn CS08.3 Why Socrates never charged a fee: factors contributing to challenges for research integrity and publication ethics Deborah Poff 9. Plagiarism and falsification: Behaviour and detection CS09.1 Personality traits predict attitude towards plagiarism of self and others in biomedicine: plagiarism, yes we can? Martina Mavrinac, Gordana Brumini, Mladen Petrovečki CS09.2 Investigating the concept of and attitudes toward plagiarism for science teachers in Brazil: any challenges for research integrity and policy? Christiane Coelho Santos, Sonia Vasconcelos CS09.3 What have we learnt?: The CrossCheck Service from CrossRef Rachael Lammey CS09.4 High p-values as a sign of data fabrication/falsification Chris Hartgerink, Marcel van Assen, Jelte Wicherts 10. Codes for research integrity and collaborations CS10.1 Research integrity in cross-border cooperation: a Nordic example Hanne Silje Hauge CS10.3 Research integrity, research misconduct, and the National Science Foundation's requirement for the responsible conduct of research Aaron Manka CS10.4 A code of conduct for international scientific cooperation: human rights and research integrity in scientific collaborations with international academic and industry partners Raffael Iturrizaga 11. Countries' efforts to establish mentoring and networks CS11.1 ENRIO (European Network of Research Integrity Offices): a network facilitating common approaches on research integrity in Europe Nicole Foeger CS11.2 Helping junior investigators develop in a resource-limited country: a mentoring program in Peru A. Roxana Lescano, Claudio Lanata, Gissella Vasquez, Leguia Mariana, Marita Silva, Mathew Kasper, Claudia Montero, Daniel Bausch, Andres G Lescano CS11.3 Netherlands Research Integrity Network: the first six months Fenneke Blom, Lex Bouter CS11.4 A South African framework for research ethics and integrity for researchers, postgraduate students, research managers and administrators Laetus OK Lategan 12. Training and education in research integrity at an early career stage CS12.1 Research integrity in curricula for medical students Gustavo Fitas Manaia CS12.2 Team-based learning for training in the responsible conduct of research supports ethical decision-making Wayne T. McCormack, William L. Allen, Shane Connelly, Joshua Crites, Jeffrey Engler, Victoria Freedman, Cynthia W. Garvan, Paul Haidet, Joel Hockensmith, William McElroy, Erik Sander, Rebecca Volpe, Michael F. Verderame CS12.4 Research integrity and career prospects of junior researchers Snezana Krstic 13. Systems and research environments in institutions CS13.1 Implementing systems in research institutions to improve quality and reduce risk Louise Handy CS13.2 Creating an institutional environment that supports research integrity Debra Schaller-Demers CS13.3 Ethics and Integrity Development Grants: a mechanism to foster cultures of ethics and integrity Paul Taylor, Daniel Barr CS13.4 A culture of integrity at KU Leuven Inge Lerouge, Gerard Cielen, Liliane Schoofs 14. Peer review and its role in research integrity CS14.1 Peer review research across disciplines: transdomain action in the European Cooperation in Science and Technology (COST) "New Frontiers of Peer Review (PEERE)" Ana Marusic, Flaminio Squazzoni CS14.2 Using blinding to reduce bias in peer review David Vaux CS14.3 How to intensify the role of reviewers to promote research integrity Khalid Al-Wazzan, Ibrahim Alorainy CS14.4 Credit where credit's due: professionalizing and rewarding the role of peer reviewer Chris Graf, Verity Warne 15. Research ethics and oversight for research integrity: Does it work? CS15.1 The psychology of decision-making in research ethics governance structures: a theory of bounded rationality Nolan O'Brien, Suzanne Guerin, Philip Dodd CS15.2 Investigator irregularities: iniquity, ignorance or incompetence? Frank Wells, Catherine Blewett CS15.3 Academic plagiarism Fredric M. Litto 16. Research integrity in Europe CS16.1 Whose responsibility is it anyway?: A comparative analysis of core concepts and practice at European research-intensive universities to identify and develop good practices in research integrity Itziar De Lecuona, Erika Löfstrom, Katrien Maes CS16.2 Research integrity guidance in European research universities Kris Dierickx, Noémie Bonn, Simon Godecharle CS16.3 Research Integrity: processes and initiatives in Science Europe member organisations Tony Peatfield, Olivier Boehme, Science Europe Working Group on Research Integrity CS16.4 Promoting research integrity in Italy: the experience of the Research Ethics and Bioethics Advisory Committee of the Consiglio Nazionale delle Ricerche (CNR) Cinzia Caporale, Daniele Fanelli 17. Training programs for research integrity at different levels of experience and seniority CS17.1 Meaningful ways to incorporate research integrity and the responsible conduct of research into undergraduate, graduate, postdoctoral and faculty training programs John Carfora, Eric Strauss, William Lynn CS17.2 "Recognize, respond, champion": Developing a one-day interactive workshop to increase confidence in research integrity issues Dieter De Bruyn, Bracke Nele, Katrien De Gelder, Stefanie Van der Burght CS17.4 "Train the trainer" on cultural challenges imposed by international research integrity conversations: lessons from a project José Roberto Lapa e Silva, Sonia M. R. Vasconcelos 18. Research and societal responsibility CS18.1 Promoting the societal responsibility of research as an integral part of research integrity Helene Ingierd CS18.2 Social responsibility as an ethical imperative for scientists: research, education and service to society Mark Frankel CS18.3 The intertwined nature of social responsibility and hope in science Daniel Vasgird, Stephanie Bird CS18.4 Common barriers that impede our ability to create a culture of trustworthiness in the research community Mark Yarborough 19. Publication ethics CS19.1 The authors' forum: A proposed tool to improve practices of journal editors and promote a responsible research environment Ibrahim Alorainy, Khalid Al-Wazzan CS19.2 Quantifying research integrity and its impact with text analytics Harold Garner CS19.3 A closer look at authorship and publication ethics of multi- and interdisciplinary teams Lisa Campo-Engelstein, Zubin Master, Elise Smith, David Resnik, Bryn Williams-Jones CS19.4 Invisibility of duplicate publications in biomedicine Mario Malicki, Ana Utrobicic, Ana Marusic 20. The causes of bad and wasteful research: What can we do? CS20.1 From countries to individuals: unravelling the causes of bias and misconduct with multilevel meta-meta-analysis Daniele Fanelli, John PA Ioannidis CS20.2 Reducing research waste by integrating systems of oversight and regulation Gerben ter Riet, Tom Walley, Lex Marius Bouter CS20.3 What are the determinants of selective reporting?: The example of palliative care for non-cancer conditions Jenny van der Steen, Lex Bouter CS20.4 Perceptions of plagiarism, self-plagiarism and redundancy in research: preliminary results from a national survey of Brazilian PhDs Sonia Vasconcelos, Martha Sorenson, Francisco Prosdocimi, Hatisaburo Masuda, Edson Watanabe, José Carlos Pinto, Marisa Palácios, José Lapa e Silva, Jacqueline Leta, Adalberto Vieyra, André Pinto, Mauricio Sant'Ana, Rosemary Shinkai 21. Are there country-specific elements of misconduct? CS21.1 The battle with plagiarism in Russian science: latest developments Boris Yudin CS21.2 Researchers between ethics and misconduct: A French survey on social representations of misconduct and ethical standards within the scientific community Etienne Vergès, Anne-Sophie Brun-Wauthier, Géraldine Vial CS21.3 Experience from different ways of dealing with research misconduct and promoting research integrity in some Nordic countries Torkild Vinther CS21.4 Are there specifics in German research misconduct and the ways to cope with it? Volker Bähr, Charité 22. Research integrity teaching programmes and their challenges CS22.1 Faculty mentors and research integrity Michael Kalichman, Dena Plemmons CS22.2 Training the next generation of scientists to use principles of research quality assurance to improve data integrity and reliability Rebecca Lynn Davies, Katrina Laube CS22.3 Fostering research integrity in a culturally-diverse environment Cynthia Scheopner, John Galland CS22.4 Towards a standard retraction form Hervé Maisonneuve, Evelyne Decullier 23. Commercial research and integrity CS23.1 The will to commercialize: matters of concern in the cultural economy of return-on-investment research Brian Noble CS23.2 Quality in drug discovery data reporting: a mission impossible? Anja Gilis, David J. Gallacher, Tom Lavrijssen, Malwitz David, Malini Dasgupta, Hans Mols CS23.3 Instituting a research integrity policy in the context of semi-private-sector funding: an example in the field of occupational health and safety Paul-Emile Boileau 24. The interface of publication ethics and institutional policies CS24.1 The open access ethical paradox in an open government effort Tony Savard CS24.2 How journals and institutions can work together to promote responsible conduct Eric Mah CS24.3 Improving cooperation between journals and research institutions in research integrity cases Elizabeth Wager, Sabine Kleinert 25. Reproducibility of research and retractions CS25.1 Promoting transparency in publications to reduce irreproducibility Veronique Kiermer, Andrew Hufton, Melanie Clyne CS25.2 Retraction notices issued for publications by Latin American authors: what lessons can we learn? Sonia Vasconcelos, Renan Moritz Almeida, Aldo Fontes-Pereira, Fernanda Catelani, Karina Rocha CS25.3 A preliminary report of the findings from the Reproducibility Project: Cancer biology Elizabeth Iorns, William Gunn 26. Research integrity and specific country initiatives CS26.1 Promoting research integrity at CNRS, France Michèle Leduc, Lucienne Letellier CS26.2 In pursuit of compliance: is the tail wagging the dog? Cornelia Malherbe CS26.3 Newly established research integrity policies and practices: oversight systems of Japanese research universities Takehito Kamata 27. Responsible conduct of research and country guidelines CS27.1 Incentives or guidelines? Promoting responsible research communication through economic incentives or ethical guidelines? Vidar Enebakk CS27.3 Responsible conduct of research: a view from Canada Lynn Penrod CS27.4 The Danish Code of Conduct for Research Integrity: a national initiative to promote research integrity in Denmark Thomas Nørgaard, Charlotte Elverdam 28. Behaviour, trust and honesty CS28.1 The reasons behind non-ethical behaviour in academia Yves Fassin CS28.2 The psychological profile of the dishonest scholar Cynthia Fekken CS28.3 Considering the implications of Dan Ariely's keynote speech at the 3rd World Conference on Research Integrity in Montréal Jamal Adam, Melissa S. Anderson CS28.4 Two large surveys on psychologists' views on peer review and replication Jelte Wicherts Brett Buttliere 29. Reporting and publication bias and how to overcome it CS29.1 Data sharing: Experience at two open-access general medical journals Trish Groves CS29.2 Overcoming publication bias and selective reporting: completing the published record Daniel Shanahan CS29.3 The EQUATOR Network: promoting responsible reporting of health research studies Iveta Simera, Shona Kirtley, Eleana Villanueva, Caroline Struthers, Angela MacCarthy, Douglas Altman 30. The research environment and its implications for integrity CS30.1 Ranking of scientists: the Russian experience Elena Grebenshchikova CS30.4 From cradle to grave: research integrity, research misconduct and cultural shifts Bronwyn Greene, Ted Rohr PARTNER SYMPOSIA Partner Symposium A Organized by EQUATOR Network, Enhancing the Quality and Transparency of Health Research P1 Can we trust the medical research literature?: Poor reporting and its consequences Iveta Simera P2 What can BioMed Central do to improve published research? Daniel Shanahan, Stephanie Harriman P3 What can a "traditional" journal do to improve published research? Trish Groves P4 Promoting good reporting practice for reliable and usable research papers: EQUATOR Network, reporting guidelines and other initiatives Caroline Struthers Partner Symposium C Organized by ENRIO, the European Network of Research Integrity Officers P5 Transparency and independence in research integrity investigations in Europe Krista Varantola, Helga Nolte, Ursa Opara, Torkild Vinther, Elizabeth Wager, Thomas Nørgaard Partner Symposium D Organized by IEEE, the Institute of Electrical and Electronics Engineers Re-educating our author community: IEEE's approach to bibliometric manipulation, plagiarism, and other inappropriate practices P6 Dealing with plagiarism in the connected world: An Institute of Electrical and Electronics Engineers (IEEE) perspective Jon Rokne P7 Should evaluation of raises, promotion, and research proposals be tied to bibliometric indictors? What the Institute of Electrical and Electronics Engineers (IEEE) is doing to answer this question Gianluca Setti P8 Recommended practices to ensure conference content quality Gordon MacPherson Partner Symposium E Organized by the Committee on Freedom and Responsibility in the Conduct of Science of ICSU, the International Council for Science Research assessment and quality in science: perspectives from international science and policy organisations P9 Challenges for science and the problems of assessing research Ellen Hazelkorn P10 Research assessment and science policy development Carthage Smith P11 Research integrity in South Africa: the value of procedures and processes to global positioning Robert H. McLaughlin P12 Rewards, careers and integrity: perspectives of young scientists from around the world Tatiana Duque Martins Partner Symposium F Organized by the Online Resource Center for Ethics Education in Engineering and Science / Center for Engineering, Ethics, and Society of the National Academy of Engineering P13 Research misconduct: conceptions and policy solutions Tetsuya Tanimoto, Nicholas Steneck, Daniele Fanelli, Ragnvald Kalleberg, Tajammul Hussein Partner Symposium H Organized by ORI, the Office of Research Integrity; Universitas 21; and the Asia Pacific Research Integrity Network P14 International integrity networks: working together to ensure research integrity Ping Sun, Ovid Tzeng, Krista Varantola, Susan Zimmerman Partner Symposium I Organized by COPE, the Committee on Publication Ethics Publication without borders: Ethical challenges in a globalized world P15 Authorship: credit and responsibility, including issues in large and interdisciplinary studies Rosemary Shinkai Partner Symposium J Organized by CITI, the Cooperative Institutional Training Initiative Experiences on research integrity educational programs in Colombia, Costa Rica and Peru P16 Experiences in Peru Roxana Lescano P17 Experiences in Costa Rica Elizabeth Heitman P18 Experiences in Columbia Maria Andrea Rocio del Pilar Contreras Nieto Poster Session B: Education, training, promotion and policy PT.01 The missing role of journal editors in promoting responsible research Ibrahim Alorainy, Khalid Al-Wazzan PT.02 Honorary authorship in Taiwan: why and who should be in charge? Chien Chou, Sophia Jui-An Pan PT.03 Authorship and citation manipulation in academic research Eric Fong, Al Wilhite PT.04 Open peer review of research submission at medical journals: experience atBMJ Open andThe BMJ Trish Groves PT.05 Exercising authorship: claiming rewards, practicing integrity Désirée Motta-Roth PT.07 Medical scientists' views on publication culture: a focus group study Joeri Tijdink, Yvo Smulders Poster Session B: Education, training, promotion and policy PT.09 Ethical challenges in post-graduate supervision Laetus OK Lategan PT.10 The effects of viable ethics instruction on international students Michael Mumford, Logan Steele, Logan Watts, James Johnson, Shane Connelly, Lee Williams PT.11 Does (uncertainty in) language reflect the quality of research? Gerben ter Riet, Sufia Amini, Lotty Hooft, Halil Kilicoglu PT.12 Integrity complaints as a strategic tool in policy decision conflicts Janneke van Seters, Herman Eijsackers, Fons Voragen, Akke van der Zijpp and Frans Brom Poster Session C: Ethics and integrity intersections PT.14 Regulations of informed consent: university-supported research processes and pitfalls in implementation Badaruddin Abbasi, Naif Nasser Almasoud PT.15 A review of equipoise as a requirement in clinical trials Adri Labuschagne PT.16 The Research Ethics Library: online resource for research ethics education Johanne Severinsen, Espen Engh PT.17 Research integrity: the view from King Abdulaziz City for Science and Technology Daham Ismail Alani PT. 18 Meeting global challenges in high-impact publications and research integrity: the case of the Malaysian Palm Oil Board HJ. Kamaruzaman Jusoff PT.19 University faculty perceptions of research practices and misconduct Anita Gordon, Helen C. Harton Poster Session D: International perspectives PT.21 The Commission for Scientific Integrity as a response to research fraud Dieter De Bruyn, Stefanie Van der Burght PT. 22 Are notions of the responsible conduct of research associated with compliance with requirements for research on humans in different disciplinary traditions in Brazil? Karina de Albuquerque Rocha, Sonia Maria Ramos de Vasconcelos PT.23 Creating an environment that promotes research integrity: an institutional model of Malawi Liverpool Welcome Trust Limbanazo Matandika PT.24 How do science policies in Brazil influence user-engaged ecological research? Aline Carolina de Oliveira Machado Prata, Mark William Neff Poster Session E: Perspectives on misconduct PT.26 What "causes" scientific misconduct?: Testing major hypotheses by comparing corrected and retracted papers Daniele Fanelli, Rodrigo Costas, Vincent Larivière PT.27 Perception of academic plagiarism among dentistry students Douglas Leonardo Gomes Filho, Diego Oliveira Guedes PT. 28 (Quite) a few bad apples?: Prevalence, patterns and attitudes towards scientific misconduct among doctoral students at a German university hospital Volker Bähr, Niklas Keller, Markus Feufel, Nikolas Offenhauser PT. 29 Analysis of retraction notices published by BioMed Central Maria K. Kowalczuk, Elizabeth C. Moylan PT.31 "He did it" doesn't work: data security, incidents and partners Katie Speanburg Poster Session F: Views from the disciplines PT.32 Robust procedures: a key to generating quality results in drug discovery Malini Dasgupta, Mariusz Lubomirski, Tom Lavrijssen, David Malwitz, David Gallacher, Anja Gillis PT.33 Health promotion: criteria for the design and the integrity of a research project Maria Betânia de Freitas Marques, Laressa Lima Amâncio, Raphaela Dias Fernandes, Oliveira Patrocínio, and Cláudia Maria Correia Borges Rech PT.34 Integrity of academic work from the perspective of students graduating in pharmacy: a brief research study Maria Betânia de Freitas Marques, Cláudia Maria Correia Borges Rech, Adriana Nascimento Sousa PT.35 Research integrity promotion in theEpidemiology and Health Services, the journal of the Brazilian Unified Health System Leila Posenato Garcia PT.36 When are clinical trials registered? An analysis of prospective versus retrospective registration of clinical trials published in the BioMed Central series, UK Stephanie Harriman, Jigisha Patel PT.37 Maximizing welfare while promoting innovation in drug development Farida Lada Other posters that will be displayed but not presented orally: PT.38 Geoethics and the debate on research integrity in geosciences Giuseppe Di Capua, Silvia Peppoloni PT.39 Introducing the Professionalism and Integrity in Research Program (P.I. Program) James M. DuBois, John Chibnall, Jillon Van der Wall PT.40 Validation of the professional decision-making in research measure James M. DuBois, John Chibnall, Jillon Van der Wall, Raymond Tait PT.41 General guidelines for research ethics Jacob Holen PT. 42 A national forum for research ethics Adele Flakke Johannessen, Torunn Ellefsen PT.43 Evaluation of integrity in coursework: an approach from the perspective of the higher education professor Claudia Rech, Adriana Sousa, Maria Betânia de Freitas Marques PT.44 Principles of geoethics and research integrity applied to the European Multidisciplinary Seafloor and Water Column Observatory (EMXO), a large-scale European environmental research infrastructure Silvia Peppoloni, Giuseppe Di Capua, Laura Beranzoli F1 Focus track on improving research systems: the role of funders Paulo S.L. Beirão, Susan Zimmerman F2 Focus track on improving research systems: the role of countries Sabine Kleinert, Ana Marusic F3 Focus track on improving research systems: the role of institutions Melissa S. Anderson, Lex Bouter